1 answer:
Answer:
p = 8
Step-by-step explanation:
![p/4 + 6 = 8\\p/4 + 4 * 6 /4 = 8](https://tex.z-dn.net/?f=p%2F4%20%2B%206%20%3D%208%5C%5Cp%2F4%20%2B%204%20%2A%206%20%2F4%20%3D%208)
You might be interested in
Hope this helps with your questions :)
Answer:
(1 - 2n)^3 equals
(1 -2n) * (1 -2n) * (1 -2n)
Step-by-step explanation:
Answer:
Y-1=5/3(x-3) (aka b)
Step-by-step explanation:
Answer:
60
Step-by-step explanation:
![a=7\\b=4\\ab+2b^2\\(7)*(4)+2*(4)^2\\28+2*16\\28+32\\=\fbox{60}](https://tex.z-dn.net/?f=a%3D7%5C%5Cb%3D4%5C%5Cab%2B2b%5E2%5C%5C%287%29%2A%284%29%2B2%2A%284%29%5E2%5C%5C28%2B2%2A16%5C%5C28%2B32%5C%5C%3D%5Cfbox%7B60%7D)
Answer:
C
Step-by-step explanation:
-2 + 7 = 5